2018
DOI: 10.1124/jpet.118.251116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Neutral Amino Acid Transporters ASCT1 and ASCT2 Are Effective in In Vivo Models of Schizophrenia and Visual Dysfunction

Abstract: The -methyl-d-aspartate receptor coagonist d-serine is a substrate for the neutral amino acid transporters ASCT1 and ASCT2, which may regulate its extracellular levels in the central nervous system (CNS). We tested inhibitors of ASCT1 and ASCT2 for their effects in rodent models of schizophrenia and visual dysfunction, which had previously been shown to be responsive to d-serine. L-4-fluorophenylglycine (L-4FPG), L-4-hydroxyPG (L-4OHPG), and L-4-chloroPG (L-4ClPG) all showed high plasma bioavailability when ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Abnormalities in ERVH48-1 dosage in TS21 may have implications in tissues other than the placenta in subjects with Down syndrome. Syn-1 and the syn-1/SUPYN receptor, ASCT2, are known to be expressed in the human brain 40 42 and changes in syn-1, a closely-related ERVW-1 envelope protein, MSRV, and ASCT2 have been linked to neurodegenerative disorders 41 , 43 and schizophrenia 44 . It is certainly possible, therefore, that overexpression of cell-associated or secretory SUPYN in TS21 could alter syn-1 activities in the brain and could therefore be associated with the neurodevelopmental and neurodegenerative aspects of Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in ERVH48-1 dosage in TS21 may have implications in tissues other than the placenta in subjects with Down syndrome. Syn-1 and the syn-1/SUPYN receptor, ASCT2, are known to be expressed in the human brain 40 42 and changes in syn-1, a closely-related ERVW-1 envelope protein, MSRV, and ASCT2 have been linked to neurodegenerative disorders 41 , 43 and schizophrenia 44 . It is certainly possible, therefore, that overexpression of cell-associated or secretory SUPYN in TS21 could alter syn-1 activities in the brain and could therefore be associated with the neurodevelopmental and neurodegenerative aspects of Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…14 ASCT1 is also relevant for the reuptake of cysteine in the brain; the levels of this amino acid, indeed, need to be kept under strict control due to toxicity. 13 The described function of ASCT1 is confirmed by some pathological conditions characterized by alterations of brain development and function, 14 such as schizophrenia, 16 visual dysfunction, 16 amyotrophic lateral sclerosis (ALS), 17 and microcephaly in children. 18 In line with this, an inherited disease, namely, SPATCCM (OMIM 616657), has been also linked with alterations of ASCT1 gene.…”
Section: Localization and Subcellular Localization In Physiological Conditionsmentioning
confidence: 94%
“…25,26 This alternative function, in line with the novel glutamate/proton transport recently demonstrated in vitro, 26 may underline a role for ASCT2 in neurological disorders and brain cancers. 16,27…”
Section: Localization and Subcellular Localization In Physiological Conditionsmentioning
confidence: 99%
“…The glutamine transporter ASCT2 has become increasingly important as a potential cancer drug target. Several studies have shown that targeting by siRNA [13,21,[49][50][51] and small molecule inhibitors [24,52], limits cell growth in rapidly growing tumor tissue. However, there are still substantial gaps with respect to our understanding of substrate and inhibitor specificity and mechanisms of interaction with ASCT2.…”
Section: Discussionmentioning
confidence: 99%